DETERMINED TO LEARN: ACCESSING EDUCATION DESPITE LIFE- THREATENING DISASTERS - SchWeber, Claudine (Online Learning, 2008)
The ‘right to education’ proclaimed by the 1948 Universal Declaration of Human Rights requires access to learning as well as the support systems. Since access can be interrupted by various circumstances, the possibility of providing continuity despite external dangers by using online distance education, offers an intriguing and valuable option. For example, life-threatening disasters, such as war or hurricanes, can interrupt or halt ongoing higher education coursework. Despite that reality, some students remain determined to continue the learning. How can institutions respond to this determination fast enough to be of use and effective enough to maintain their educational reputations? Empire State College’s (New York) activities in its Lebanon Residence Program after the 2006 war and Xavier University in New Orleans’ actions in the aftermath of Hurricane Katrina provide valuable answers. Together with the unique Sloan Semester—created to temporarily provide educational continuity for hurricane affected students—these programs also offer lessons on resilience and survival in a crisis.